'No country for old men'? The multiplier effects of pensions in Portuguese municipalities. (19th April 2020) - Mourao, Paulo Reis; Vilela, Cilina
Abstract: One of the major findings of this paper, which studied the multiplier effects of pensions received at each Portuguese municipality since 2003, is that pensions stimulate the incomes of municipalities. We studied these effects also considering the spillovers from/to the surrounding areas. After discussing several models of spatial analysis, we chose the Dynamic Spatial Durbin Model. Our results were obtained after considering a proper set of control variables.